The Development of Management Balanced Scorecard Guidelines in Schools under Secondary Educational Service Area 27 - Piya Godsa (Journal of Education, Mahasarakham University, 2018)
The development of school management using Balanced Scorecard in the Secondary Educational Service Area 27 schools aims to study the present conditions and disirable conditions of school management, to develop of school management using Balanced Scoredcards in the Secondary Educational Service Area 27 schools that is comprising with 2 terms of the study. Fristly, studying of present conditions and disirable conditions of school management using Balanced Scoredcard in the Secondary Educational Service Area 27. Secondly, the development of school management using balanced scoredcard in the Secondary Education Service Area 27. The research instruments are the questionaires, the interview froms, the record forms and the assessment forms. The statistics are used for data analysis are mean, percentages, standard deviations and Priority Needs Index. The results showed that 1. Present condition in school management using the balanced scorecard of schools under secondary educational service area 27 the overviews were at the highest level and desirable condition of school management using the balanced scorecard of schools under secondary educational service area 27 the overviews were at the highest level. 2. Develop of management balanced scorecard guidelines in schools under secondary educational service area 27. Academic administration is divided into 4 perspectives. 1) perspectives on student 11 guidelines 2) perspectives on internal education management process 10 guidelines 3) perspectives on learning and development 8 guidelines and 4) perspectives on budget and resource 7 guidelines.